Decoding Sanitation Practices: A Comparative Assessment of Knowledge, Attitudes, and Behaviours - Dedy Suprayogi; Utama Teguh Taruna (Universitas Nahdlatul Ulama Surabaya, 2026)
Adequate sanitation is a crucial factor in improving public health. Knowledge, practice, and behaviors play a key role in the success of sanitation programs. Fundamental aspects of sanitation are the availability of trash bins, which can reduce disease transmission risks. Moreover, in the Lumajang district, the village of Tegalrandu and RanuRanupakis shows an 80% trash bin ownership rate, aligning with national and global standards. However, differences in community knowledge, attitudes, and behaviors between the two villages remain unclear. This study aims to decode sanitation practices by assessing and comparing the knowledge, attitudes, and behaviors of the communities in Tegalrandu dan RanuRanupakis villages regarding environmental sanitation. An analytic study with a cross-sectional design was conducted, involving 80 respondents selected through simple random sampling, with 40 participants from each village. The Mann-Whitney statistical test was employed to analyze differences between the two groups. The results indicated that the significance values for knowledge (0,766), attitude (0,120), and behavior (0,298) were all higher than the α value of 0,05, which suggests no statistically significant differences between the two communities. The findings reveal that despite geographical differences, both villages exhibit similar sanitation knowledge, attitudes, and behaviors. This implies that external factors such as economic conditions, socio-cultural aspects, government policies, and sanitation program interventions may have a greater influence on community sanitation practices. Future efforts should focus on enhancing public awareness and sustainability in sanitation programs to achieve long-term environmental health improvements.